Name: Maria Rainsdon
Who is asking: Student
Level: Middle

I don't understand how to solve these multiple step problems. I wasn't there when my teacher explained it and I am really lost. Here is one of the probs I don't understand: 3m+6=-m-6. Could you please reply asap? Thanks

Hi Maria,

You have the equation

3m + 6 = -m - 6

and you want to "solve for m". That is you want an equation that is equivalent to

3m + 6 = -m - 6

but which has the form

m = "a number"

I am going to call this equation the target equation.
   One feature I see in the target equation that is not true of your original equation is that the letter m only appears on the left of the equal sign. To "remove" m from the right side of the original equation I add m to both sides to get

3m + 6 + m = -m - 6 + m

On the left side 3m + m = 4m and on the right side -m + m = 0 and thus this equation simplifies to

4m + 6 = - 6

This equation is equivalent to the original equation since I obtained it from the original equation by adding the same amount (m) to both sides.
   I now want to "remove" the 6 from the left side of the equation and I do this by adding -6 to both sides of the equation to get

4m + 6 - 6 = - 6 - 6

which simplifies to

4m = - 12

All that remains now is to "remove" the 4 from the left side while maintaining the equality of the two sides. This I do by dividing both sides by 4 to get

4m/4 = - 12/4


m = -3

I hope this helps,

Go to Math Central